2015
DOI: 10.1371/journal.pone.0124971
|View full text |Cite
|
Sign up to set email alerts
|

The Clostridium difficile Protease Cwp84 Modulates both Biofilm Formation and Cell-Surface Properties

Abstract: Clostridium difficile is responsible for 15-20% of antibiotic-associated diarrheas, and nearly all cases of pseudomembranous colitis. Among the cell wall proteins involved in the colonization process, Cwp84 is a protease that cleaves the S-layer protein SlpA into two subunits. A cwp84 mutant was previously shown to be affected for in vitro growth but not in its virulence in a hamster model. In this study, the cwp84 mutant elaborated biofilms with increased biomass compared with the parental strain, allowing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 35 publications
3
85
0
Order By: Relevance
“…The bacterial burden was quantified by seeding caecal and faecal samples on selective plates from day 2 until day 15 post‐infection. The 630Δ erm strain proliferated in the mice as previously described (Pantaleon et al ., ), reaching a bacterial burden of infection of 5 × 10 8 bacteria per gram of faeces after 2 days of infection (Fig. A).…”
Section: Resultsmentioning
confidence: 95%
“…The bacterial burden was quantified by seeding caecal and faecal samples on selective plates from day 2 until day 15 post‐infection. The 630Δ erm strain proliferated in the mice as previously described (Pantaleon et al ., ), reaching a bacterial burden of infection of 5 × 10 8 bacteria per gram of faeces after 2 days of infection (Fig. A).…”
Section: Resultsmentioning
confidence: 95%
“…Dapa et al (2013) found that the cwp84 mutant strain had no defect in planktonic growth but had an important decrease in biofilm accumulation as compared to the R20291 parent strain, and that the biofilm defect for the cwp84 strain was fully complemented by restoring the wild type gene on the chromosome, suggesting that a mature S-layer is essential for C. difficile biofilm formation in this strain. In turn, Pantaléon et al (2015) found that the biofilm formed by the cwp84 mutant strain was 72-fold increased over that of the 630Derm parent or complemented cwp84 mutant, and suggested that the accumulation of uncleaved SlpA (occurring in the biofilm matrix of the cwp84 mutant) may promote biofilm formation and enhance the bacterial interactions. Since Cwp84 is involved in proteolytic maturation of several other surface proteins, the effect of cwp84 mutation in biofilm formation could go beyond the defect in SLP formation.…”
Section: Biofilm Formationmentioning
confidence: 96%
“…In addition to the capsule, C. difficile has an S-layer, a proteinaceous paracrystalline array composed of two components, a high molecular weight component, and low molecular weight component, both formed from post-transcriptional cleavage of the slpA gene (Calabi et al, 2001). Also present in the S-layer are up to 28 paralogous proteins (Fagan et al, 2011) which have been implicated in a number of virulence-related activities including adhesion, biofilm formation and degradation of host proteins (Cafardi et al, 2013;Pantaleon et al, 2015;Waligora et al, 2001). Flagella and motility are not essential for the pathogenesis of CDI as they are absent from clade 5 strains, but have been shown to play a role in colonisation in clade 2 strains (Stevenson et al, 2015).…”
Section: Other Virulence Factorsmentioning
confidence: 99%